Protection of whistleblower in Malaysia: comparative studies on revelation to third party, motive and reward / Mohamad Amri Alfikri Mohamad Dasuki, Muhammad Nor Sollihin Salleh, Luqman Hadi Jusoh. - Mohamad Dasuki, Mohamad Amri Alfikri; Salleh, Muhammad Nor Sollihin; Jusoh, Luqman Hadi (2012)
The study is carried out to assess the comprehensiveness of Whistleblower Protection Act 2010 (WPA 2010) in relation to its provisions regarding the avenues to make a disclosure, motives of the disclosure and award to whistleblowers. The research will be based on qualitative type of research by focusing on data gathered from various written sources as well as interviews conducted with legal experts. The research will focus on the protection of whistleblowers specifically on the issue of revelation to third parties, motive and reward or monetary incentives to the whistleblowers. The provisions which provide that the disclosure can only be made to enforcement agency is found lacking as other avenues such as towards media, employers (internal organization) and lawyers appear to be among the appropriate avenues that should be included too. In terms of motive, the Act puts limitation to the objective of the law as it tends to focus on the informer itself rather than the information they intend to reveal. As for reward, the provisions that leave the matter entirely on the discretion of enforcement of agency are lamentable as there is no clear provision stipulates from which the fund may come. The research concludes that the Act has not adequately protected whistleblowers and thus, some recommendations have been proposed at the end of this research in view of improving the Act and thereby encourage people to become the whistleblowers